The Effect of Teaching Materials Based on Local Value Integrated by Character Education through PBL Models on Students' High Order Thinking Skill - Khairil Hadi; Dazrullisa; Hasruddin; Binari Manurung (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
This study aims to know the effect of biology teaching materials based on local wisdom integrated character education through problem-based learning models on students' high order thinking skills. This study uses a quantitative approach and belongs to the type of quasi-experimental research. The research design is the one group’s pre-test-post-test design. The research sample consisted of 111 students from five schools in West Aceh. The data collection used a validation sheet of the lesson plan and high-level thinking test questions. Research data was analysed by statistical average values, normality, homogeneity, and paired sample t test. The research results indicated that the using of biology teaching materials based on local wisdom integrated with character education through problem based learning models has a very significant effect on students' high-level thinking (P=0.00). The instruction that used local wisdom, character education and PBL model have a positive role in the motivating of students, cooperation, discipline, fond of reading, student achievement, and problems solving in accordance with the expected learning outcomes.